Original articlePSA bouncing after brachytherapy HDR and external beam radiation therapy: a study of 121 patients with minimum 5-years follow-up - Makarewicz, Roman; Lebioda, Andrzej; Terlikiewicz, Joanna; Biedka, Marta; Wiśniewski, Tomasz (Journal of Contemporary Brachytherapy, 2009)
Purpose: To determine the clinical and dosimetric factors that predict prostate-specific antygen (PSA) bouncing following brachytherapy HDR and three-dimensional conformal radiation therapy (3D-CRT) for prostate cancer patients. Material and methods: The evaluated population consisted of 121 prostate cancer patients with a minimum of 5 years of follow-up and at least 6 post-treatment PSA levels. All patients were treated using 3D-CRT combined with brachytherapy HDR. A bounce was defined as a PSA rise of ł 0.2 ng/ml above the nadir followed by a subsequent 120 decline of ł 0.2 ng/ml. The evaluated clinical factors included: patient age, Gleason score, maximum initial pretreatment PSA value (iPSAmax), clinical stage, prostate volume, median time to PSA nadir, median PSA nadir value and patient follow-up in months. The dosimetric factors evaluated included the percentage of the prostate volume receiving 100% (V100), 150% (V150) and 200% (V200) of the prescribed minimal peripheral dose. Results: Statistically significant predictive factors for PSA bounce were age, V100, V150, V200, iPSAmax and median time to PSA nadir. Logistic regression model for multivariate analysis revealed that only age, iPSAmax and V200 were statistically significant predictors for PSA bounce. There were not statistical differences between median nadir among patients who exhibited a PSA bounce and did not but non-bouncer reached PSA nadir earlier than bouncer, respectively median time was 12.1 vs. 17.2 months. Conclusions: PSA bouncing occurs in approximately a one third (1/3) of patients treated with 3D-CRT and brachytherapy HDR. Bouncing is associated with age, higher pretreatment PSA level and increased V200 factor.